Lives in transition : longitudinal analysis from historical sources - Baskerville, Peter A.; Inwood, Kris E., 1951- (Carleton library series ;, 2015)
Collective histories and broad social change are informed by the ways in which personal lives unfold. This book examines individual experiences within such collective histories during the nineteenth and twentieth centuries.